ASME 2010 7th International Symposium on Fluid-Structure Interactions, Flow-Sound Interactions, and Flow-Induced Vibration and 2010
DOI: 10.1115/fedsm-icnmm2010-30887
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Side-View Mirror Flow-Induced Vibration Phenomena

Abstract: The primary objective of this research is to develop an understanding of the flow mechanisms which induce side-view mirror vibrations. The unsteady nature of the flow over side-view mirrors causes unsteady aerodynamic load distributions and flow-induced vibrations on the mirror assembly. These vibrations generate blurred rear-view images and higher noise levels, affecting the safety and comfort of the passengers. Geometrical design features of side-view mirrors exacerbate the flow-induced vibration levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Experimental results showed that aerodynamic noise caused by the rear view mirror was increased obviously with the increased vehicle speed. Tomac [13] quantitatively studied the impact of those design features of rear view mirrors on the vibration amplitude; developed a methodology for testing mirror vibrations in a small, low-speed wind tunnel using only the mirror of interest; and delved into the interactions between the bluff body mirror geometry and its wake. Onur [14] has tested the flow fields over a rearview side mirror in a wind tunnel and the results showed that the static pressures are presented different distribution over the rear view mirror and took smaller values at the separation points of the boundary layer from the mirror surface.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that aerodynamic noise caused by the rear view mirror was increased obviously with the increased vehicle speed. Tomac [13] quantitatively studied the impact of those design features of rear view mirrors on the vibration amplitude; developed a methodology for testing mirror vibrations in a small, low-speed wind tunnel using only the mirror of interest; and delved into the interactions between the bluff body mirror geometry and its wake. Onur [14] has tested the flow fields over a rearview side mirror in a wind tunnel and the results showed that the static pressures are presented different distribution over the rear view mirror and took smaller values at the separation points of the boundary layer from the mirror surface.…”
Section: Introductionmentioning
confidence: 99%